Evolutionary prediction and experimental identification of stable phases in Pd-Ni/γ-Al2O3 bimetallic catalysts - Gulevich, Semyon A.; Shcherbakova-Sandu, Mariya P.; Meshcheryakov, Eugene P.; Abzaev, Yuri A.; Guda, Sergey A.; Buzaev, Aleksander A.; Borilo, Lyudmila P.; Knyazev, Alexey S. 1978-; Kurzina, Irina A. (Вестник Томского государственного университета. Химия)
This work presents a combined theoretical and experimental study of the structural features of Pd-Ni bimetallic nanoclusters. A comprehensive exploration of the configurational space of Pd-Ni nanoclusters (13-56 atoms) across a wide range of compositions (Pd:Ni = 1:1 - 50:1) was performed using the evolutionary algorithm USPEX in conjunction with density functional theory (DFT) calculations. Our approach revealed thermodynamically stable and metastable intermetallic phases with a low-symmetry triclinic structure (space group P1), characterized by complex atomic ordering and a propensity for segregation. The predicted structures were used for a detailed interpretation of experimental X-ray diffraction (XRD) data, enabling the identification of the phase composition of synthesized Pd-Ni/γ-Al2O3 samples. We demonstrate that the phase equilibrium in the system non-linearly depends on the overall component ratio, encompassing both single-phase states (e.g., Ni-Pd13 at Pd:Ni = 1:1 and Ni-Pd33 at 10:1) and regions of phase coexistence (e.g., Ni-Pd50 and Ni-Pd33 at 5:1). These findings elucidate the atomistic origins of the synergistic interaction between Pd and Ni and provide a foundation for the rational digital design of highly efficient and selective bimetallic catalysts.